A comparative study on the performance of microbial fuel cell for the treatment of reactive orange 16 dye using mixed and pure bacterial species and its optimization using response surface methodology - Shahi A.; Velayudhaperumal Chellam P.; Verma A.; Singh R.S. (My University, 2025)
The present work provides an insight on the removal of dye and energy recovery simultaneously by Acinetobacter pitii in microbial fuel cells. It focuses on decolorization of reactive orange 16 dye and electricity production in a microbial fuel cell using bacterial isolate Acinetobacter pitii. This isolate removes 92.70% of color at a fixed concentration of 500 ppm of dye within 24 h on the 20th day of operation. The maximum voltage and current density obtained from the species is found to be 0.4379 V and 0.973 A/m3 at 1000 Ω. The central composite design was used to model the process for the removal of 243 ppm of dye from the initial dye concentration of 295 ppm at pH of 7.5, time 71.27 h, with simultaneous production of 1.06 A/m3 of current density. Analytical techniques such as Chemical Oxygen Demand (COD), Fourier-transform infrared spectroscopy (FTIR), Liquid chromatography and mass spectroscopy analysis (LCMS), Scanning electron microscope (SEM), and carbon-di-oxide (CO2) determination were used to study about the nature of the removal of reactive orange 16 dye in a microbial fuel cell. The toxicity of the degraded sample was assessed using Phytotoxicity analysis. © 2021